2017
DOI: 10.15835/nbha45110726
|View full text |Cite
|
Sign up to set email alerts
|

Newly Isolated Paecilomyces lilacinus and Paecilomyces javanicus as Novel Biocontrol Agents for Plutella xylostella and Spodoptera litura

Abstract: Biocontrol offers an attractive alternative to the use of chemical pesticides in agricultural pest management. The development of high levels of resistance to chemical pesticides have forced researchers to find more alternative biological control agents. The aims of this study were to isolate Paecilomyces spp. with high virulence against diamondback moth (Plutella xylostella) and Oriental leafworm moth (Spodoptera litura), and to investigate suitable agro-industrial residues as a substrate used for solid state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…have been reported to control different insect pests, but only a few studies have reported the pathogenicity of C. javanica against D. citri (Faria & Wraight, ; Gandarilla‐Pacheco, Galán‐Wong, López‐Arroyo, Rodríguez‐Guerra, & Quintero‐zapata, ; Medina‐Córdova, Rosales‐Mendoza, Hernández‐Montiel, & Angulo, ; Meyer, Hoy, & Boucias, ; Vega et al, ). Nguyen et al () isolated two highly virulent strains of C. javanica against diamondback moth Plutella xylostella with respective LT 50 values of 2.52 and 2.55 days.…”
Section: Discussionmentioning
confidence: 99%
“…have been reported to control different insect pests, but only a few studies have reported the pathogenicity of C. javanica against D. citri (Faria & Wraight, ; Gandarilla‐Pacheco, Galán‐Wong, López‐Arroyo, Rodríguez‐Guerra, & Quintero‐zapata, ; Medina‐Córdova, Rosales‐Mendoza, Hernández‐Montiel, & Angulo, ; Meyer, Hoy, & Boucias, ; Vega et al, ). Nguyen et al () isolated two highly virulent strains of C. javanica against diamondback moth Plutella xylostella with respective LT 50 values of 2.52 and 2.55 days.…”
Section: Discussionmentioning
confidence: 99%
“…Paecilomyces is capable of parasitizing fungi [ 71 ], nematodes and arthropods [ 72 , 73 ]. After recognition and pathogen-antagonist interaction take place, penetration and/or secretion of enzyme complexes occurs, leading to antagonist growth at the expense of its host [ 74 , 75 ].…”
Section: Biological Control Mechanisms Of the Genus Paecmentioning
confidence: 99%
“…Numerous orders of arthropods that are vulnerable to the use of Paecilomyces spp. ( Table 3 ), including hemiptera, have been described, such as aleurodids [ 246 ], aphids [ 238 ], thysanoptera [ 242 ], diptera [ 247 ], lepidoptera [ 73 ], hymenoptera [ 248 ] and coleoptera [ 235 ].…”
Section: Biological Control Of Diseases Caused By Arthropodsmentioning
confidence: 99%
“…Entomopathogenic fungi are promising agents in regulation populations of S. litura (Chaudhari et al, 2016; Nguyen et al, 2017; Namasivayam et al, 2018; Sahayaraj et al, 2018; Kaur et al, 2019; Yang et al, 2019). Fungi belonging to genus Beauveria (Hypocreales: Cordycipitaceae) are one of the most common insect pathogenic fungal species, which can act as an alternative to pesticides against S. litura (Borja et al, 2018; Dhar et al, 2019; Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%